2011
DOI: 10.1007/7854_2011_144
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics: Genetics Versus Life Experiences

Abstract: Epigenetics is the field of research that examines alterations in gene expression caused by mechanisms other than changes in DNA sequence. ADHD is highly heritable; however, epigenetics are considered relevant in potentially explaining the variance not accounted for by genetic influence. In this chapter, some of the well-known processes of epigenetics, such as chromosome organization, DNA methylation, and effects of transcriptional factors are reviewed along with studies examining the role of these processes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 149 publications
0
16
0
1
Order By: Relevance
“… 42 , 43 Non-genetically mediated low birth weight and related delayed brain maturation 44 have also been associated with both ASD, 45 , 46 and ADHD, 47 , 48 even after strict correction for potential confounders, 49 but the underlying risk mechanism is still unclear. The negative impact of toxins such as air pollutants, tobacco, heavy metals and pesticides on ASD 50 and ADHD 51 has been studied rather extensively in animals, and to a much lesser extent in humans. Yet, results so far are mixed, and these findings should therefore be treated with great caution.…”
Section: Discussionmentioning
confidence: 99%
“… 42 , 43 Non-genetically mediated low birth weight and related delayed brain maturation 44 have also been associated with both ASD, 45 , 46 and ADHD, 47 , 48 even after strict correction for potential confounders, 49 but the underlying risk mechanism is still unclear. The negative impact of toxins such as air pollutants, tobacco, heavy metals and pesticides on ASD 50 and ADHD 51 has been studied rather extensively in animals, and to a much lesser extent in humans. Yet, results so far are mixed, and these findings should therefore be treated with great caution.…”
Section: Discussionmentioning
confidence: 99%
“…ADHD presents a disorder characterized by marked levels of impulsiveness [111,112], that persists over the individual’s lifespan [113115]. The relevance of epigenetic mechanisms for ADHD etiopathogenesis has been discussed [20,116]; chromosome organization, DNA methylation and transcriptional factors all contribute to the pathophysiology of the disorder [117]. Environmental risk factors for high trajectories of impulsivity-hyperactivity and inattention symptoms were premature birth, low birth weight, prenatal tobacco exposure, non-intact family, young maternal age at birth of the target child, paternal history of antisocial behavior, and maternal depression [118] all of which are clear-cut examples of environmental adverse conditions.…”
Section: Introductionmentioning
confidence: 99%
“…As reviewed by Elia and colleagues [33] and Archer and colleagues [34], epigenetic factors, impacting during prenatal as well as postnatal periods, are considered important in the etiology of human ADHD and welldesigned studies are clarifying the effects of some contributing factors. For example, the finding that maternal smoking during pregnancy is an environmental factor conferring risk for ADHD in the child is being disproven by studies taking into account inheritance factors [35], similar to what is reported for prenatal alcohol exposure [36].…”
Section: Epigeneticsmentioning
confidence: 99%